Diagnostic challenges in neoplastic meningitis presenting as intracranial hypertension. Issue 3 (10th March 2021) - Andugulapati, Santosh Sriram; Chheda, Akash; Desai, Karan; Ravat, Sangeeta Hasmukh
Abstract : A diagnosis of idiopathic intracranial hypertension should be considered only after careful exclusion of all possible aetiologies. We report a case of neoplastic meningitis presenting as intracranial hypertension with inconclusive repeated cerebrospinal fluid (CSF) cytology and MRI of brain, emphasising the importance of meticulous CSF analysis and role of early whole-body PET–CT scan for diagnosis of systemic malignancy.